Flood studies conference papers and discussion on the 'Flood studies report' and discussion on 'Reservoir flood standards' : proceedings of the Conference organized by the Institution of Civil Engineers London, 7-8 May, 1975 - Darwent, Thelma J. (Institution of Civil Engineers, 1975)
These papers cover rainfall, snowmelt, give a prediction of the runoff hydrograph from a design storm, discuss flood routing methods and highlight the extension of short records and flood estimation from catchment characteristics.
Keywords: Floods -- Great Britain.; elektronické knihy; electronic books